Psychological Dynamics of Middle-Aged Balinese Women Following Spousal Infidelity - Ratih Saraswaty; Putu Diana Wulandari; Ni Made Irene Novianti Astaningtias (Bali Medical and Wellness Journal, 2025)
Introduction: Marital infidelity is a multifaceted phenomenon and a primary catalyst for divorce worldwide. This study explores the complex psychological dynamics of middle-aged women who have experienced chronic spousal infidelity within the specific cultural context of Bali, Indonesia. Case Description: This research utilizes a qualitative case study approach, focusing on a 44-year-old Balinese woman (LS) who endured five distinct episodes of infidelity over a 22-year marriage. Data collection involved in-depth interviews and observation, supplemented by a comprehensive psychological battery, including Graphic Tests, Wartegg, Standard Progressive Matrices (SPM), Sack’s Sentence Completion Test (SSCT), and the Beck Depression Inventory (BDI). Discussion: Clinical assessment revealed that the subject suffers from severe anxiety and clinical depression. Her personality profile is characterized by low self-esteem, chronic indecision, and a maladaptive preoccupation with past traumas. The psychological dynamics identified include profound social withdrawal, emotional dysregulation, and somatic symptoms such as insomnia, fatigue, and loss of appetite. The findings suggest that the repetitive nature of the betrayal led to a state of learned helplessness and a diminished capacity for proactive problem-solving or future planning. Conclusion: The study concludes that chronic infidelity in a long-term marriage produces deep-seated psychological scars that impair both daily functioning and social integration. For women in traditional cultural settings like Bali, these dynamics are compounded by a lack of adaptive coping mechanisms, necessitating targeted psychological intervention to address the intersection of trauma and self-identity.